Comparison of aeroponics system and use of substrates in Cherry tomato cultivation (Solanum lycopersicum L. var. cerasiforme) (Agro Productividad, 2025)
Objective: to compare the influence of three substrates, lava rock [in Mexico called ‘tezontle’] (TZ), peat + vermiculite (TV), and coconut fiber (FC) with the aeroponics technique (AE) as growing media for Cherry tomatoes (Solanum lycopersicum L. var. cerasiforme), under controlled nutritional conditions.Design /Methodology/ Approach: after 31 days in the seedbed, tomato seedlings were transplanted. At 28 days after transplant (DAT) in all four cultivation systems, the number of leaves was recorded. Then, at 42 and 49 DAT plant height and stem diameter (DIAM) of the main plant and lateral shoots were measured, as well as counting the number of flowers. Fruit production was assessed between days 88 and 120 DAT.Results: AE and TV significantly improved the number of leaves. Taller plants were obtained in TV and FC, while the TV substrate improved DIAM. The number of lateral shoots was higher in AE; but their highest length and DIAM were recorded in TV. AE increased the number of flowers at 42 DAT, whereas TV did so at 49 DAT.Limitations/ Implications of the study: the only factor of variation was the growing substrate. In addition, the nutrient solution preserved the balance between cations and anions. The aeroponics conditions of this research allowed free root growth in an ad hoc designed system.Findings/ Conclusions: a cluster analysis revealed that the significant differences between cultivation systems occur mainly in vegetative variables, compared to production variables. Thus, suggesting that the cultivation technique does not affect fruit production. The AE system is a promising option to study the interaction between crops and bio-stimulants, aiming to improve agricultural sustainability.